2012
DOI: 10.1002/mrd.22077
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase II transcriptional silencing in growing and fully grown germinal vesicle oocytes isolated from gonadotropin‐stimulated and non‐stimulated gilts

Abstract: Global transcription silencing occurs in the oocyte during its final phase of growth. The particular mechanism of this silencing is not well understood. Here, we investigated the silencing of RNA polymerase II transcription in porcine oocytes. First, we investigated the transcriptional activity of germinal vesicle oocytes derived from stimulated and non-stimulated gilts, but no transcriptional activity was observed. Second, we focused on the fate of RNA polymerase II in growing and fully grown oocytes. Active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…It appears likely that many of the molecular processes driving oocyte maturation have the potential to be regulated by the dynamic pattern of miRNA expression. Upon germinal vesicle breakdown, it is it widely recognized that there is a widespread decrease in the level of oocyte transcriptional activity that lasts until the onset of zygotic transcription which is generally thought to happen at the 8–16 cell stage [ 32 , 33 ]. MicroRNA-155 is a major miRNA induced at this time point and one of the major functional clusters identified in miR-155 targets is the regulation of transcription from RNA polymerase II transcription factor activity, suggesting associations between the two processes.…”
Section: Discussionmentioning
confidence: 99%
“…It appears likely that many of the molecular processes driving oocyte maturation have the potential to be regulated by the dynamic pattern of miRNA expression. Upon germinal vesicle breakdown, it is it widely recognized that there is a widespread decrease in the level of oocyte transcriptional activity that lasts until the onset of zygotic transcription which is generally thought to happen at the 8–16 cell stage [ 32 , 33 ]. MicroRNA-155 is a major miRNA induced at this time point and one of the major functional clusters identified in miR-155 targets is the regulation of transcription from RNA polymerase II transcription factor activity, suggesting associations between the two processes.…”
Section: Discussionmentioning
confidence: 99%
“…Porcine ovaries were obtained at a local slaughterhouse and transported to the laboratory in a Dulbecco's phosphate-buffered saline supplemented with 0.01% polyvinyl-alcohol (PBS-PVA) at 30–35°C. After three times washing with PBS-PVA, the GV stage oocytes were aspirated from large antral follicles (3–5 mm, in diameter) as previously reported (Barnetova et al , 2012). The oocytes surrounded by several layers of compact cumulus cells (cumulus–oocyte complexes – COCs) were selected and washed three times in M2 medium.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we asked whether RNAPII degradation is physiologically relevant to NSN-to-SN transition in vivo. Previous work reported that the levels of phosphorylated RNAPII are lower in SN oocytes as compared to NSN oocytes [38][39][40][41][42][43][44][45][46][47] , but whether this observation reflects simply dephosphorylation or depletion at protein level is not clear. To this end, we compared the abundance of phosphorylated as well as of total RNAPII in NSN and SN oocytes by immunofluorescence staining and immunoblotting.…”
Section: Segregase-and Proteasome-mediated Degradation Of Rnapii Is N...mentioning
confidence: 99%